1931 Ark. Acts 705-06, § 2 - (:unkn) unknown (My University, 1931)
Act of Mar. 26, 1931, No. 225, § 2: Prohibited storing, keeping, possessing, having in possession, or permitting another to store, keep, or posses, any firearm type commonly known as a machine gun.
Keywords: MACHINE GUN RESTRICTION